Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan di Bunda Hotel Padang - Shelly Tri Utami; yuliana Yuliana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Abstract. The purpose this study was to determine the effect of work motivation on employee performance at Bunda Hotel Padang. Type of research quantitative with causal associative approach. The number of samples this study were 31 people who were taken using saturated sampling techniques. This research data uses primary data for work motivation variables with data collection techniques through questionnaires with Likert scales that have been tested for validity and reliability. Employee performance variables use secondary data obtained from HRD Bunda Hotel Padang. Data analysis techniques using simple linear regression test with help of SPSS version 16.00 computer program. Results showed that work motivation was in the sufficient category with percentage of 55%. While employee performance is good category with a percentage of 61% and there is positive and significant effect of work motivation on the performance of employees in Bunda Hotel Padang by 16.2% while 83.8% influenced by other factors. Keywords: Work Motivation, Employee Performance, Hotel